On the embedding of Waterman class in the class Hωp - Goginava, U. (Український математичний журнал, 2005)
In this paper the necessary and sufficient condition for the inclusion of class ΛBV in the class Hωp is found. Знайдено необхідну i достатню умову для включення класу ΛBV до класу Hωp.